Role of Trataka and Jala Neti in Digital Eye Syndrome - Maurya, Akarshit; Joshi, Saurbh (International Research Journal of Ayurveda & Yoga, 2025)
The technology contributes negative cons along with positive benefits. As per available data, major cons are on Chakshuindriya (eyes), according to the National Institute of Occupational Safety and Health. DES affects 90% of people who spend 3 or more hours on a computer screen. It can be managed through Trataka and Jala Neti. During Trataka practices, it stimulates the lacrimal gland, which helps to produce a normal amount of tears to lubricate the eyes, and also tones up the optic nerve for better vision and saves from sensitivity toward light. Jala Neti means cleansing of Cavities (oral and nasal), which gives a soothing effect on the eyes. That means it protects from the burning sensation and redness of the eyes, symptoms of DES. Hence, these two yogic practices give a positive impact and are useful for a more desirable effect. The purpose of this study is to explain the comparative efficacy of Tratak and Jala Neti for the management of DES. The literary material is collected from related literature, research papers, digital-e-sources, and manuscripts. On the basis of the available documents, the critical analysis is done, and a suitable conclusion will be drawn. This study suggests that Tratak and Jala Neti improve the ability to make visual adjustments, and remove all symptoms such as dryness, burning sensation, sensitivity to light, itching, and swelling.